Neocortical Lamination: Insights from Neuron Types and Evolutionary Precursors - Shepherd, Gordon M.; Rowe, Timothy B. (Frontiers in Neuroanatomy, 2017)
The neocortex is characterized by lamination of its neuron cell bodies in six layers, but there are few clues as to how this comes about and what is its function. Recent studies provide evidence that evolution from simple three-layer cortex may give insight into this problem. Three-layer cortex arose in the olfactory, hippocampal and dorsal cortex of the early amniote forebrain based on a cortical module of excitatory and inhibitory inputs to an intratelencephalic (IT) type of pyramidal neuron with feedback excitation and inhibition and related interneurons. We summarize recent evidence suggesting the hypothesis that the developmental program of three-layer olfactory cortex was co-opted to form six-layer mammalian neocortex, elaborating IT cortical units in layers 2–6 while adding layer 4 stellate cells, layer 5B pyramidal tract (PT) cells and layer 6 corticothalamic (CT) cells.